OCRL1 mutation in a boy with dent disease, mild mental retardation, but without cataracts - Lozanovski, Vladimir J.; Ristoska-Bojkovska, N.; Korneti, P.; Gucev, Z.; Tasic, V. (World journal of pediatrics, 2011)
Oculocerebrorenal (Lowe) syndrome is an X-linked multisystem disease characterized by renal proximal tubulopathy, mental retardation, and congenital cataracts. We present a 19-year-old boy who was found to have low molecular weight proteinuria, hypercalciuria, mild generalized hyperaminoaciduria and intermittent microscopic hematuria at the age of 3.